Temperature and Pressure Dependence of the Coefficient of Non-linearity Acoustic Parameters in Higher Alkanes - Jha, L.K. (Asian Journal of Chemistry, 2010)
Temperature coefficient of the non-linearity acoustic parameters (B/A), (C/A) and (D/A) are calculated for heptane, octane, nonane, dodecane and hexadecane. Pressure dependence of these coefficients are also studied. The results show that the acoustic properties of these five higher alkanes cease to vary at pressure P 400 bar.